PENGARUH MODEL PEMBELAJARAN LEARNING COMMUNITY TERHADAP KEMAMPUAN KONEKSI MATEMATIS DAN PEMECAHAN MASALAH SISWA - Rofiah, Khofidotur; Hartati, Sulis Janu; Hanifah, Sri Yuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Mathematics learning currently still uses the conventional model through lectures and giving assignments so that learning activities do not provide opportunities for students to be actively involved in developing their potential. Mathematics learning using conventional learning models is dominated by teachers and students are not actively involved. Learning through lectures and assignments does not direct students to develop mathematical connection abilities and solve everyday problems using mathematical concepts. The objectives of this research include: 1) To prove the influence of the learning community learning model on the mathematical connection abilities of class IX students of SMP Negeri 1 Bangkalan, 2) To prove the influence of the learning community learning model on the problem solving abilities of class IX students of SMP Negeri 1 Bangkalan, and 3 ) To prove the effect of the learning community learning model on the mathematical connection and problem solving abilities of class IX students at SMP Negeri 1 Bangkalan. This research uses a quantitative research approach and experimental research type with a nonequivalent control group design. The sample in this study was class IX-A with 35 students as the experimental class and class IX-D with 35 students as the control class. The researcher used independent sample t test and MANOVA data analysis techniques to test the research hypothesis and obtain conclusions from the research results, including: 1) There is an influence of the learning community learning model on the mathematical connection abilities of class IX students at SMP Negeri 1 Bangkalan, 2) There is an influence of the learning model community on the problem solving abilities of class IX students at SMP Negeri 1 Bangkalan, and 3) There is an influence of the learning community learning model on the mathematical connection and problem solving abilities of class IX students at SMP Negeri 1 Bangkalan.